Breaking Seed Dormancy in Argemone mexicana L. Seeds (University of Khartoum Journal of Agricultural Sciences, 2023)
95U. of K. J. Agric. Sci. 22(1), 95-111, 2014Breaking Seed Dormancy in Argemone mexicana L. SeedsTarig Mohamed Mohamed Ahmed1 and Hanadi Ibrahim El DessougiDepartment of Agronomy, Faculty of Agriculture,University of Khartoum, Shambat, SudanAbstract: Laboratory tests were conducted in 2010, at the SeedLaboratory, Department of Agronomy, Faculty of Agriculture, Universityof Khartoum, Sudan, to investigate the effect of different methods ofbreaking seed dormancy in Argemone mexicana seeds. The methods usedwere soaking of seeds for six hours in tap water followed by drying forsix hours, hydration of seeds for six hours and drying for six hours thenhydration and dehydration for the same period, soaking of seeds in hotwater (60 ̊C) for six durations (10, 20, 30, 40, 50 and 60 minutes), treatingthe seeds with H2 SO 4 (70%) for 5, 20, 40 and 60 minutes, treating theseeds for two hours using 250, 500 and 1000 ppm of gibberelic acid(GA3 ), treating the seeds with combinations of GA3 (250, 500 and 1000ppm) and H2 SO 4 for 20 and 40 minutes. The experiment was executed ina completely randomized design. The analysis of variance showed thatboth GA3 and combination treatments (GA3 /H2 SO 4 ) had significantlyhigher seed germination percentage and germination rate than the controland other treatments. The highest germination percentage (27.7%) andgermination rate (74x10-2 ) were obtained when the seeds were treatedwith 250 ppm GA3 . Hydration and dehydration and soaking in hot waterand sulphuric acid were not effective in breaking seed dormancy inArgemone mexicana seeds. The results indicated no physical or chemicaldormancy in the seed, but physiological or morpho-physiologicaldormancy.